2016
DOI: 10.1038/nature20796
|View full text |Cite
|
Sign up to set email alerts
|

Persistent microbiome alterations modulate the rate of post-dieting weight regain

Abstract: In tackling the obesity pandemic, significant efforts are devoted to the development of effective weight reduction strategies, yet many dieting individuals fail to maintain a long-term weight reduction, and instead undergo excessive weight regain cycles. The mechanisms driving recurrent post-dieting obesity remain largely elusive. Here, we identify an intestinal microbiome signature that persists after successful dieting of obese mice, which contributes to faster weight regain and metabolic aberrations upon re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
320
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(353 citation statements)
references
References 35 publications
18
320
2
3
Order By: Relevance
“…Physiological variation in human host physiology can be dependent on the time of the day 54 (for example, sleep–wake cycles, food intake or changes in hormone levels), over different seasons 55 or over the course of a lifetime 56 . Although multiple studies have delineated the effect of the host diet on the composition of the microbiome 55,57 , little work has been done to mechanistically resolve the effect of a change in diet on the microbial interaction network. Mice subjected to a Western-like diet with a high fat and low fibre content over several generations showed a progressive loss of microbial diversity, which could not be recovered after the reintroduction of a high-fibre diet 58 .…”
Section: Network Dynamics and Cross-feedingmentioning
confidence: 99%
“…Physiological variation in human host physiology can be dependent on the time of the day 54 (for example, sleep–wake cycles, food intake or changes in hormone levels), over different seasons 55 or over the course of a lifetime 56 . Although multiple studies have delineated the effect of the host diet on the composition of the microbiome 55,57 , little work has been done to mechanistically resolve the effect of a change in diet on the microbial interaction network. Mice subjected to a Western-like diet with a high fat and low fibre content over several generations showed a progressive loss of microbial diversity, which could not be recovered after the reintroduction of a high-fibre diet 58 .…”
Section: Network Dynamics and Cross-feedingmentioning
confidence: 99%
“…A major route of chemical communication between this vast group of microorganisms and the host is via microbial metabolism of dietary nutrients and production of metabolites. Microbial metabolites have been demonstrated to play roles as signaling molecules and metabolic substrates (15,18,19,52,163,169), a topic which has been thoroughly reviewed (4,163,170). There is evidence that exposure to antibiotics (171), cold ambient temperatures (172), natural seasonal variation in food intake and ambient temperature during hibernation (173175), natural seasonal variation in food sources (176), geographical and cultural differences in dietary habits or dietary scarcity (4850,177,178), hormonal cues (31,58), alteration in dietary macronutrient composition (10,47,53,179), food additives (16,34), and more can affect gut microbial communities.…”
Section: Regulation Of Chromatin Modification By Endogenous Metabolitmentioning
confidence: 99%
“…Additionally, there are known differences in microbiota composition, gene-richness, and metabolite production associated with agrarian or plant-based diets vs. “Westernized” diets (4751). There are also lasting consequences of obesity and a “Western” lifestyle on the microbiome, both in the setting of post-diet weight gain (52) and multigenerational consumption of a diet low in microbial accessible carbohydrates (MACs), which result in a progressive loss of diversity that cannot be replenished by reintroduction of dietary MACs (53). In addition to dietary factors, altered gut anatomy in the setting of gastric bypass surgery influences the gut microbiota and its function (54,55).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies in rodents have demonstrated that loss of microbiota diversity due to dietary changes can be transferred to later generations , with progressive loss of diversity [35]. Also, a Western diet could lead to a permanent loss of bacteria important to microbiome function [36], and possibly induce inheritable metabolic changes via the epigenome [37]. In sum, the environment created in the gut by ultra-processed foods could be an evolutionarily unique selection ground for microbes with behaviors that promote diverse forms of inflammation-related disease.…”
Section: Factors That Promote Inflammation Through Diet-microbiome-homentioning
confidence: 99%